Systematic Literature Review Analisis Perbandingan Implementasi Manajemen Risiko TI pada Sektor Perbankan - Rian Nopiardi; Debora Marianthi; Ni Kadek Sri Manik; Assyifa Restu Maharani Putri; Andika Galuh; Reinhard Imanuel (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
This research is a Systematic Literature Review (SLR) research which aims to analyze the implementation of Information Technology (IT) Risk Management in the banking sector. Through the SLR process, researchers collected, evaluated, and synthesized evidence from 20 selected national journal articles obtained from Google Scholar using the Harzing's Publish or Perish application. The subjects of this research are various national journal articles which discuss IT Risk Management in the banking sector, while the objects are the implementation process, evaluation, strategy, analysis and influence of implementing IT Risk Management on financial performance and operational sustainability of banks. The research results provide important insights for professionals and stakeholders in strengthening the security and sustainability of bank operations in the ever-changing digital era. Recognizing the influence of external factors such as regulation and digital transformation, the research highlights the need for adaptation to the dynamics of the banking industry to improve IT Risk Management. The findings have the potential to contribute significantly to efforts to develop best practices in managing information technology risk in the banking sector.